2014
DOI: 10.1371/journal.pone.0084761
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Functional Potential and Community Composition in Permafrost-Affected Soils of the NW Canadian Arctic

Abstract: Permafrost-affected soils are among the most obvious ecosystems in which current microbial controls on organic matter decomposition are changing as a result of global warming. Warmer conditions in polygonal tundra will lead to a deepening of the seasonal active layer, provoking changes in microbial processes and possibly resulting in exacerbated carbon degradation under increasing anoxic conditions. To identify current microbial assemblages in carbon rich, water saturated permafrost environments, four polygona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
81
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(103 citation statements)
references
References 69 publications
21
81
1
Order By: Relevance
“…Therefore, near-surface layers of soil and the rhizosphere would be expected to have the highest CH 4 oxidation activity (Shukla et al, 2013;Gulledge et al, 1997). The 5 relative abundance of the pmoA marker gene for CH 4 oxidation decreased with soil depth in HCP trough soils (Yang et al, 2017) and in permafrost-affected soils from the Canadian Arctic (Frank-Fahle et al, 2014), consistent with that conceptual model. Thus, we would expect that the active layers of FCP and HCP in the BEO tundra have the highest rates of CH 4 oxidation.…”
Section: Discussion 20supporting
confidence: 60%
“…Therefore, near-surface layers of soil and the rhizosphere would be expected to have the highest CH 4 oxidation activity (Shukla et al, 2013;Gulledge et al, 1997). The 5 relative abundance of the pmoA marker gene for CH 4 oxidation decreased with soil depth in HCP trough soils (Yang et al, 2017) and in permafrost-affected soils from the Canadian Arctic (Frank-Fahle et al, 2014), consistent with that conceptual model. Thus, we would expect that the active layers of FCP and HCP in the BEO tundra have the highest rates of CH 4 oxidation.…”
Section: Discussion 20supporting
confidence: 60%
“…The zero-curtain zone of the active layer provides favorable conditions for heterotrophic soil respiration during the late fall to early winter. Thus, appreciable gas fluxes have been measured on the snow surface during winter (Zimov et al, 1993(Zimov et al, , 1996Fahnestock et al, 1999). It is likely that frost cracks provide passages for gases to reach the atmosphere as there is often a strong pulse of gases during early spring thaw.…”
Section: Biochemical Processes At Low Temperaturesmentioning
confidence: 99%
“…Although most of the studies on cryostructure are focused on its physical aspects, cryostructure also has a role in soil biogeochemical processes. As the unfrozen water in ice lenses or ice layers in the cryostructure engage in heat and mass transfer in the winter (Romanovsky and Osterkamp, 2000), unfrozen water can serve as a channel for biological activity and thereby affect carbon cycling during winter months (Fahnestock et al, 1999).…”
Section: Soil Structure In the Upper Permafrostmentioning
confidence: 99%
“…Estimates suggest that 25 % of the northern hemisphere is underlain by permafrost (soil that has remained frozen for at least two consecutive years; reviewed in Jansson and Tas 2014) and may comprise up to 50 % of subsurface organic carbon stocks (Frank-Fahle et al 2014). The extent of permafrost distribution has decreased over the last century and it is predicted that near-surface permafrost thawing will be a continuous feature in the coming years as a feature of global warming (Steven et al 2008).…”
Section: Permafrostmentioning
confidence: 99%
“…The microbial response to this permafrost thawing is still unresolved, including the contributions of particular microbial groups to CO 2 and CH 4 fluxes. Interestingly, cyanobacteria have been absent from numerous phylogenetic surveys using Arctic permafrost samples, with actinobacteria and proteobacteria predominating (Steven et al 2008;Frank-Fahle et al 2014). A metagenomic study also reported no cyanobacteria signature in a 2-m deep permafrost sample (Yergeau et al 2010), although the possible detection of nitrogenase (nifH) belonging to cyanobacteria was proposed.…”
Section: Permafrostmentioning
confidence: 99%